2010
DOI: 10.1007/s11102-010-0234-7
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic pituitary abnormalities in tubercular meningitis at the time of diagnosis

Abstract: Tubercular meningitis (TBM) is the most dreaded form of extra pulmonary tuberculosis associated with high morbidity and mortality. Various hypothalamic pituitary hormonal abnormalities have been reported to occur years after recovery from disease but there are no systematic studies in the literature to evaluate the pituitary hypothalamic dysfunction in patients with TBM at the time of presentation. Therefore, the present study was designed to evaluate hypothalamic pituitary abnormalities in newly diagnosed pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…In a recent study from India, hypopituitarism was observed in about 30% of newly diagnosed TBM. [7] The study stated TBM to be a severe stressful condition and conveniently used the controversial cortisol cut-off values for diagnosing adrenal insufficiency. The thyroid dysfunction could well be interpreted as sick euthyroid syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study from India, hypopituitarism was observed in about 30% of newly diagnosed TBM. [7] The study stated TBM to be a severe stressful condition and conveniently used the controversial cortisol cut-off values for diagnosing adrenal insufficiency. The thyroid dysfunction could well be interpreted as sick euthyroid syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…[1] It is at best limited to case series involving childhood hypopituitarism,[2] Sheehan syndrome,[34] post radiotherapy,[5] pituitary adenomas,[6] or tubercular meningitis (TBM). [7] A study from Spain documented an incidence and prevalence of hypopituitarism to be 4.21 and 45.5 cases per 100 000 population, respectively. [8] Hypopituitarism follows a smoldering course unless it has an onset with pituitary apoplexy; hence, more often it is likely to be missed.…”
Section: Introductionmentioning
confidence: 99%
“…In an Indian study, multiple pituitary hormone deficiency was reported in 29.3% of cases, and no patient had evidence of diabetes insipidus (72). After treatment with antituberculous drugs, the pituitary tuberculoma may disappear with the reversal of hypopituitarism in some cases (71).…”
Section: Tuberculosismentioning
confidence: 97%
“…Multiple pituitary hormone deficiency was seen in 22 (29.3%) cases. [5] While tubercular abscess of the brain has been reported, primary tubercular abscess of the pituitary is extremely rare. The literature review yields only few cases of primary tubercular lesion of the pituitary and the diagnosis was reached only after surgery.…”
mentioning
confidence: 99%